Unusual epigraphic documentation: “acta notarial” (1747) of a medieval inscription in the Alburquerque’s walls - de Francisco Olmos, José María; Fernández Martínez, Rodrigo José (Revista General de Información y Documentación, 2020)
The aim of this paper is to analyze an “acta notarial” (1747) found at the Real Academia de la Historia, that contains the transcription of a medieval inscription and proves its contents. That inscription, at the time that the acta was made, was placed at the Alburquerque’s walls. We analyse the reason why it was made, comparing what it says with what was known at that time about the inscription and others inscriptions that had a relation with it, made by the same author and at the same time (the beginning of the 14th century), and so with modern studies about it.
Keywords: Alburquerque; Real Academia de la Historia; medieval epigraphy; acta notarial; epigraphic historiography